Pemberdayaan Masyarakat Melalui Kawasan Rumah Pangan Lestari (KRPL) Guna Mewujudkan Gerakan Aceh Mandiri Pangan di Kampung Jagong Jeget, Kabupaten Aceh Tengah - Fantashir Awwal Fuqara; Muhammad Reza Aulia; Anisah Nasution; Safrika Safrika; Yulia Windi Tanjung; Dewi Andriani; Ovianalisa Ovianalisa (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2024)
Food availability is a condition where household food needs are met sufficiently, both in terms of quantity and quality and affordable. The yard is one of the closest sources to produce food needs to meet family nutritional needs, and reduce shopping needs and and can increase household income. The purpose of this activity is to improve the community's capability in managing the yard and provide insight, knowledge and expertise in cultivating vegetables. The method of community service activities is observation or survey, socialization, monitoring and evaluation. The results of this activity are able to increase public awareness of family health and nutrition by 85.9%, motivate the community to cultivate vegetables by 93.3% and increase 100% of people who are able to cultivate food crops and horticulture. This community service activity is expected to provide knowledge about sustainable food houses, as well as skills in cultivating plants so that healthy and nutritious vegetables are obtained in every house in Jagong Jeget Village, Aceh Tengah Regency